MODELING RELATIONSHIP BETWEEN PUBLIC AND PUBLICLY GUARANTEED EXTERNAL DEBT OF UKRAINE AND BUDGET DEFICIT, SPENDING AND SAVINGS - KARMELYUK, Anna; PLASKON, Svitlana; SENIV, Halyna (Journal of European Economy, 2017)
The dynamics of external public and publicly guaranteed external debt of Ukraine, the budget deficit and spending and savings in Ukraine in UAN and USDollar since 1996 to the present date were analyzed and their trends were built. An emphasize was laid on the following periods: 1996–2006 – a period of sustained economic development (pre-crisis), characterized by slow growth of debt; 2007–2011 – a period of rapid growth in debt (crisis); 2012–2014 – a period of sustained growth in debt (post-crisis); since 2015 until now – a period of a new economic crisis. The predictive values of the debt were calculated for 2017– 2021. The method of harmonic scales was applied, based on the principle of aging information, and according to a point projected values of public and publicly guaranteed debt. Their intervals were calculated. The econometric models dependence of the total external public debt of the budget deficit in Ukraine and vice versa was calculated. It was established that the increasing of the budget deficit by 1% of the GDP leads to an increasing total external debt to 41.856 billion UAH or 3.8762 billion USD. It also leads to an increasing debt by 1 billion USD and to an increasing deficit in the budget to 0.2507% of the GDP. The econometric models depending on costs and savings from debt in UAH and USDollar were constructed. It was found that the growth of the total external debt of the state by 1 billion UAH was accompanied by rising costs and savings by 4.637 UAH. The distributed lag model depending the costs and savings from debt in UAH was constructed and equivalent with a delay in one year, according to the increasing total external debt by 1 billion UAH is accompanied by increasing costs and savings next year by 4.2848 billion UAH. The distributed lag model depending the costs and savings on debt in US-Dollar without displacement was constructed. It is founded that the increasing in total external public debt by 1 billion USD increases the amount of costs and savings on 3.6858 billion USD. Models that examine these figures in UAH and US-Dollars show the good consistency of increasing coefficients. The model with instrumental variables was calculated, which shows that the costs and savings are incremental in nature. It was established that the increasing in spending and savings in the current year by 1 billion UAH leads to increasing costs and savings of 1.06771 billion UAH next year. It is shown that the growth of debt by 1 billion UAH leads to increasing costs and savings to 0.0243 billion UAH. JEL: C3, С32.